Identifikasi Streptococcus Equi dari Kuda yang Diduga Menderita Strangles - Rahmat Hidayat; Fatri Alhadi (Institut Pertanian Bogor, 2012)
This study aims to determine the presence of the Streptococcus equi causes Strangles in horses. Inspection carried out by isolation and identification of bacteria from 20 samples nasal swabs of suspected horse disease Strangles. Isolation and identification of activities performed by the method of bacterial culture, Gram stain, catalase test, and with sugar test. Results obtained from a series of tests to identify the bacteria Streptococcus equi of 20 horses suspected by clinical strangles, there is a horse infected by Strangles disease.